Kadar nitric oxide serum berhubungan dengan tekanan darah pada dewasa muda dengan obesitas sentral: studi pertama di Indonesia - Nurhasanah Nurhasanah; Imelda Tresia Pardede; Feriyandi Nauli; Istiyana Hayati; Fikri Roja Nasution; Angga Rizki Hermawan (Jurnal Gizi Klinik Indonesia, 2023)
Serum nitric oxide levels are associated with blood pressure in young adults with central obesityBackground: Central obesity is a risk factor for hypertension, which is closely related to the presence of endothelial dysfunction and associated with levels of nitric oxide (NO). Objective: This research was conducted to determine the relationship between NO and blood pressure (BP) in young adults with and without central obesity and also to compare the NO levels and BP between the two groups. Methods: This cross-sectional study was conducted in Pekanbaru, Riau, Indonesia, with 80 young adult subjects aged 18-25 years by consecutive sampling, consisting of 40 subjects with central obesity (waist circumference (WC) ≥90 cm and ≥80 cm for men and women, respectively) and 40 subjects without central obesity (WC <90 cm and < 80 cm for men and women, respectively). Blood pressure was measured using a digital sphygmomanometer, and NO levels were measured using Griess methods. The statistical analysis begins with the normality test of the data, normal data was analyzed with the Pearson correlation test, and abnormal data was analyzed with the Spearman test. Differences in the levels of NO, systolic blood pressure (TDS), and diastolic blood pressure (TDD) between groups was analyzed with the Mann-Whitney-U test.Results: Most of the subjects had high NO levels (66.3%). NO levels had a positively significant relationship with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in total subjects (r = 0.503, p <0.05; r= 0.289, p<0.05, respectively) and with SBP in subjects with central obesity (r = 0.324, p <0.05) but there was no significant relationship in normal subjects. There is a significant difference between serum NO levels, SBP, and DBP between subjects with central obesity and normal subjects (p <0.05).Conclusion: NO levels have a positive significant relationship with SBP and DBP in total subjects and with SBP in young adults with central obesity.